Medication-related osteonecrosis of the jaw: A survey of knowledge, practices and opinions of dentists (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate dentists on their knowledge on biphosphonates, medication related osteonecrosis of the jaw (MRONJ), and on the treatment approaches towards patients using bisphosphonates in the Faculty of Dentistry at İzmir Katip Celebi University. Material and Methods: This was a questionnaire-based cross-sectional study conducted on 97 dentists. The surveys consists of a total of 20 questions and four sections, with statistical analysis being used on the collected data. The Chi-square and Student-t tests were utilized to compare between the groups. The significance level was set at p 0.05.Result: There was no significant difference in terms of correct answers to the questions between the dentists with professional experience in surgical procedures (Group A), and the dentists without professional experience in surgical procedures (Group B) (p> 0.05). In the second part of the questionnaire, the dentists were asked various questions in order to measure their general knowledge regarding bisphosphonates and MRONJ. There was no significant difference between the groups in terms of correct answers (p> 0.05). In the third part of the questionnaire, surgical scenarios were presented to the dentists and generally, they preferred the option in which no procedure should be performed in patients who take intravenous (IV) bisphosphonates, regardless of the duration of use. Conclusions: Increasing the awareness of medical practitioners, dentists, and patients in the use and side effects of bisphosphonates is important for preventing MRONJ. For this purpose, training strategies related to MRONJ should be established.
Keywords: Awareness; knowledge; medication related osteonecrosis of the jaw